A SERVICE ORIENTED ARCHITECTURE FOR INTERNET OF THINGS (IOT) - Balasubramaniam, Sandhya; Sarala, V; Kavitha, J.C (IJRDO -Journal of Computer Science Engineering, 2015)
Internet of things (IoT) is changing the way we identify information. It has motivated solutions for a number of everyday problems. With the advent of IoT, the internet will house several “intelligent “objects capable of making their own decisions. The basic architecture of IoT is characterized by the presence of three distinct layers, the sensing layer, the network layer and the application layer. The proposed paper aims at providing an efficient platform to develop solutions for the IoT. Service oriented architecture (SOA) has seen tremendous growth in the recent years. It has become one of the widely used platforms for development. In the proposed paper a SOA layer helps to manage the data and information. The heterogeneous nature of data in an IoT environment can be effectively handled with the help of a service framework.